Pious Simulacra: Millennial Muslim Piety on Social Media and Its Implications for Islamic Education - Khairul Rezqi Alviansyah; Dian Mohammad Hakim; Abdul Jalil (Al-Qalam Institute, 2025)
Young Muslims increasingly present their religiosity on social media, turning piety into something displayed as much as practiced. This study examines how millennial Muslims represent piety on Instagram, TikTok, and YouTube, how those representations harden into simulacra under platform logic, and what the phenomenon means for Islamic education. The research uses a qualitative approach with a hermeneutic phenomenological design. Data came from digital observation, in-depth interviews with a religious content creator, a millennial audience member, and an Islamic-education teacher, and documentation, then were analyzed through the interactive model of Miles and Huberman within an interpretive frame. Findings show that piety online is constructed from religious symbols, hijrah narratives, and aesthetic craft, and that its persuasive weight rests as much on packaging as on doctrinal content. Once reproduced, aesthetically filtered, and algorithmically distributed, the sign of piety begins to circulate independently of the devotion it once signaled, producing a condition of hyperreality that informants recognized yet could not escape. This mediated piety reaches students as decontextualized fragments, leaving them fluent in the markers of religiosity but less practiced in its substance. The study consolidates these findings into the Pious Simulacrum-to-Pedagogy model, which identifies critical digital literacy and character formation as paired responses. Its implication is that Islamic education must treat the algorithmic feed as both the source of the problem and a resource for transforming religious learning, moving students from recognizing pious signs toward grasping the substance those signs are meant to carry.